Using the "Language Inquiry" as a Teaching Device - Frogner, Ellen A.; Illinois State-Wide Curriculum Study Center in the Preparation of Secondary English Teachers, Urbana ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
The "Language Inquiry," a collection of 100 statements about attitudes toward language, was devised to help teachers evaluate themselves and determine their students' ideas about language so that they could better plan what materials and strategies to utilize in a course. By indicating the degree of his agreement with each statement in the "Inquiry" and then comparing his responses with those of 10 linguists who evaluated each item, the respondent will better understand his own ideas about language and how they agree with current expert thought. An additional section of the "Inquiry" provides an opportunity for the respondent to record three items, from among the 100, that he would like to have discussed and the reasons for his choice. People who would find such a survey of value in their teaching situations are methods teachers and other teacher educators, teachers of language-related subjects, workshop leaders, high school and college supervisors, and high school English teachers. (The "Language Inquiry" with the responses of the linguists to each item is reproduced here.) See also TE 001 654. (LH)
Availability: The Language Inquiry, P. O. Box 2027, Station A, Champaign, Ill. 61820 ($2.00). The "Language Inquiry" (the 100-item instrument) may be ordered separately for $0.25.
Contract Number: OEC-5-10-029.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Language Instruction; Language Teachers; Language Tests; Language Usage; English Instruction; Language; Questionnaires; Student Attitudes; Teacher Attitudes; Project English; Language Inquiry